Information technology: an erosion of cataloguing and classification practices? (1998)
The gradual metamorphosis of information handling techniques from the era of book arrangement according to weight, length/size, colour, etc. to the informatised epoch is explored. TINLIB software has been made the paradigm in the study and analysis of the impact of Information Technology on Library Management Packages. There has been a progression in the system of managing information in Nigeria, albeit only minimal. The information handling mechanism has also crawled-up to a level where cataloguers, classifiers and indexers need a re-orientation to be able to cope with the on-going universal informatisation of society.